Strategi Intervensi Penanganan Stunting di Indonesia: Studi Literatur - Silvia Anggraini; Muthmainnah Muthmainnah; Nurul Septiani; Tomy Suganda (SEHATI: Jurnal Kesehatan, 2024)
Stunting not only has an impact on children's physical growth and development, but also has significant long-term implications for the quality of Indonesia's human resources (HR) in the future. Comprehensive and multi-sectoral stunting management efforts involving various parties need to be carried out. To analyze more deeply the intervention strategies that have been implemented in efforts to deal with stunting in Indonesia as a form of identifying approaches that have been proven successful and are relevant for the Indonesian context. This research uses the PRISMA literature review, through a digital library database that is connected to various scientific publication pages through keywords such as "Stunting", "Stunting Intervention", "Stunting Strategy", and "Stunting Program". Eligibility criteria use various types of methods The research includes quantitative, qualitative methods and reviews related to intervention strategies for handling stunting in Indonesia. Intervention strategies for handling stunting in Indonesia include three groups of programs, namely age-specific nutrition programs, nutrition and reproductive health education as well as strengthening posyandu and community health centers. Strategies Stunting prevention interventions in Indonesia must involve all stakeholders, prioritize preventive approaches, and encourage changes in community behavior. By strengthening government commitment and innovative cross-sector collaboration, it is hoped that Indonesia can overcome the challenge of stunting in a sustainable manner.